2004
DOI: 10.2143/ac.59.5.2005226
|View full text |Cite
|
Sign up to set email alerts
|

Plasma interleukin-6 levels are increased in coronary artery ectasia

Abstract: Results of this study have demonstrated increased levels of circulating IL-6 in patients with coronary ectasia which might indicate a possible role of inflammatory processes. Absence of a significant correlation between the dimensions of the ectatic segments and IL-6 levels might be due to the narrower range of the diameters of the coronary arteries compared with the abdominal aorta.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 0 publications
3
46
0
Order By: Relevance
“…A limited number of studies have evaluated the role of inflammatory (CRP and IL-6) and proteolytic markers (MMPs, TIMPs) in the CAE patients. [8][9][10][11][12][13] They provided divergent results.…”
Section: Discussionmentioning
confidence: 99%
“…A limited number of studies have evaluated the role of inflammatory (CRP and IL-6) and proteolytic markers (MMPs, TIMPs) in the CAE patients. [8][9][10][11][12][13] They provided divergent results.…”
Section: Discussionmentioning
confidence: 99%
“…Tokgozoglu et al [17] reported elevated plasma levels of inflammatory markers such as interleukin-6 and C-reactive protein (CRP) in CEA patients comparing with those with normal coronary. In another study from Ozbay [18], significantly elevated hs-CRP levels in CEA patients than that in AS patients, and significant decreased hs-CRP levels after a 3-month statins therapy, also showing CEA patients may benefit from statins.…”
Section: Discussionmentioning
confidence: 99%
“…Whether the same mechanisms are operative in CAE is not known. However, elevation of inflammatory markers such as interleukin-6 has been shown in both AAA and CAE [18,19]. Intrinsic defects of the media or systemic factors may predispose the media to form aneurysms.…”
Section: Discussionmentioning
confidence: 99%